Asuhan Kebidanan Berkelanjutan Pada Ny. R di PMB Nurhasanah, S. Tr. Keb Bandar Lampung Tahun 2024 - Wulan Dari; Reki Meidha Anggraini; Silvera Andriyani (Pusat Riset dan Inovasi Nasional, 2025)
Comprehensive Midwifery Care is care provided continuously to mothers during pregnancy, childbirth, postpartum and newborns and family planning. The comprehensive midwifery care model aims to improve continuous care during a certain period. Comprehensive midwifery care where midwives as professionals, lead in planning, organizing and providing care for better quality of care. Continuity Of Care carried out by midwives is generally oriented to improving continuity of service in a period. Continuity Of Care has three types of services, namely management, information and relationships. Solving maternal health problems needs to use a continuous midwifery care approach which is a series of continuous and comprehensive service activities starting from pregnancy, childbirth, postpartum, newborns, and family planning, must be used to solve maternal health problems. The purpose of writing this article is to provide an overview of continuous care during pregnancy, childbirth, postpartum and newborns and family planning. This study uses a descriptive observation approach with a case study method. The subjects in this study were pregnant women at Mrs. R G1P0A0 with an age of 37 weeks up to KB at PMB Nurhasanah, STr, Keb Bandar Lampung. No complications were found from the care that had been carried out.